Trends in prevalence of deep venous thrombosis among hospitalised patients in an Asian institution - Ng, Heng Joo; Lee, Lai Heng (Thrombosis and Haemostasis, 2009)
Venous thromboembolism (VTE) has long been considered a disease of secondary importance among Asians because of its perceived low prevalence. We studied the prevalence and patterns of deep venous thrombosis (DVT) among hospitalised patients in our tertiary referral centre. Primary and secondary DVT prevalence among hospitalised patients was 0.453%, a significant rise from reported rates of 0.079% and 0.158% in 1989–1990 and 1996–1997, respectively. Malignancies and orthopaedic surgery were the most common risk factors for DVT. Further comparisons with the two earlier Singaporean studies showed no changes in the gender and ethnic background of patients but a higher proportion of elderly patients (>80 years) was recorded in the current study (11.7% vs. 7.0%, p = 0.04). Statistically significant increases were found in all medical and surgical disciplines except among obstetrics and gynaecology patients. Orthopaedic patients had the highest increase in DVT rates between the 1989–1990 and 2002–2003 periods (0.082% vs. 0.96%, p<0.01). Doppler ultrasound scans performed increased from approximately one per 100 admissions in 1996–1997 to one per 30 admissions in 2002–2003. The significant increase in period prevalence of DVT among hospitalised patients in Singapore could be accounted by methodologic differences between comparative studies, an increase in proportion of elderly patients and most importantly, a possible shift in perception of the importance of VTE among Asians, resulting in a higher index of suspicion and lower threshold for performing diagnostic tests.
Keywords: Venous thrombosis; Asians; prevalence